Implementasi Pemberian Informasi Publik Pada Badan Pemeriksa Keuangan Perwakilan Provinsi Jambi Berdasarkan Undang-Undang Nomor 14 Tahun 2008 Tentang Keterbukaan Informasi Publik - Herma Yanti (Wajah Hukum, 2020)
This research aims to determine the implementation of public information on BPK Jambi Provincial representative under UU No. 14 of 2008 on public information disclosure and the problems faced and efforts to resolve the issue. Therefore, this research is an empirical research law with a socio approach to legal research. Research data is collected through document studies and interviews with respondents and informant that are relevant to the research object. From the results of the research is known that the implementation of public information in BPK Jambi Provincial representatives has reflected the principles of providing public information services as stipulated in the UU KIP.  Public information is provided openly through the provision and provision of public information conducted directly through the Information and Communication Center (PIK) and also accessible through the BPK website, so as to enable the public to obtain a variety of public information that is managed by the BPK quickly and easily free of charge. Nevertheless, in the provision of information encountered problems, caused by the high level of public curiosity to the BPK provincial representatives have not been balanced with the level of public understanding of the task of the BPK function along with the policies and procedures of providing public information by BPK. Because it needs to be balanced with the improvement of socialization to the community so that the environment is manifested public information disclosure that more guarantees the fulfillment of community needs in obtaining information.